Curatorial Fieldwork as a Critical Practice: Learning from Post-Nostalgic Knowings in Freixo - Moreira, Inês; Coelho, Patrícia (Writingplace, 2023)
As fieldwork is becoming a situated practice and an investigative process for the comprehension of places, the present paper proposes a new reading of the urbanscape of Freixo, a marginalized territory in Porto, Portugal. Learning from Post-Nostalgic Knowings and focusing on curatorial and artistic actions, we elaborate a new understanding of the invisibilities and conditions of this territory, by proposing a curatorial fieldwork. From context-specific approaches to new methods of fieldwork, we expand the reading of curatorial actions beyond the gallery and museum spaces, to create a dialogue with the site, its local community and the artistic interventions. ‘Curatorial Fieldwork as a Critical Practice’ navigates through shared experiences, proposing new expectations of a site and simultaneously revealing the strategies of its future.